Dynamics of Microglia Activation in the Ischemic Brain: Implications for Myelin Repair and Functional Recovery - Raffaele, Stefano; Fumagalli, Marta (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke is a neurological disorder representing a leading cause of death and permanent disability world-wide, for which effective regenerative treatments are missing. Oligodendrocyte degeneration and consequent myelin disruption are considered major contributing factors to stroke-associated neurological deficits. Therefore, fostering myelin reconstruction by oligodendrocyte precursor cells (OPCs) has emerged as a promising therapeutic approach to enhance functional recovery in stroke patients. A pivotal role in regulating remyelination is played by microglia, the resident immune cells of the brain. Early after stroke, microglial cells exert beneficial functions, promoting OPC recruitment toward the ischemic lesion and preserving myelin integrity. However, the protective features of microglia are lost during disease progression, contributing to remyelination failure. Unveiling the mechanisms driving the pro-remyelination properties of microglia may provide important opportunities for both reducing myelin damage and promoting its regeneration. Here, we summarize recent evidence describing microglia activation kinetics in experimental models of ischemic injury, focusing on the contribution of these innate immune cells to myelin damage and repair. Some molecular signals regulating the pro-regenerative functions of microglia after stroke have been highlighted to provide new possible therapeutic targets involved in the protective functions of these cells. Finally, we analyzed the impact of microglia-to-OPCs communication via extracellular vesicles on post-stroke remyelination and functional recovery. The results collected in this review underline the importance of supporting the pro-remyelination functions of microglial cells after stroke.